Potential oxygen-carrying complexes by desing - Rosas García, Víctor Manuel; Elizondo Martínez, Perla; Pérez Rodríguez, Nancy; Nájera Martínez, Blanca (Universidad Autónoma de Nuevo León, 2012)
There are twenty four elements known to be necessary for human life, seven of which are transition metals. These seven elements: V, Cr, Mn, Fe, Co, Cu and Zn have an important role in living systems due to their ability to form complexes with diverse donor groups present biological systems. [Co(salen)] has been previously studied as a model compound for oxygen transport. In this work ther metallic complexes, Ni(II), Zn(II), Cu(II) and Fe(II) with N,N'-bis(salicylaldehyde)ethylenediamine (salen-H2) were synthesized. The active form of each complex was obtained by reaction with dimethylsulfoxide. The ability of these metallic complexes to act as O2 carriers was determined. From the results, the complexes of the Co(II), Fe(II) and Cu(II) with salen are able to transport oxygen with an ordering of Co(II)>Fe(II)>Cu(II)regarding the capacity to carry O2. We used the PM7 semiempirical hamiltonian to study the complexes of salen with Co(II), Cu(II), Fe(II) and Ni(II) and their potential as oxygen carriers. We performed full geometry optimizations in the gas phase for each complex, its active form with DMSO as ligand, and with dioxygen complexed with the active form. We discuss energetic features associated with the binding of dioxygen to the complexes.